2005
DOI: 10.1161/01.cir.0000159339.00703.22
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Overexpression of Diacylglycerol Kinase-ζ Inhibits Endothelin-1–Induced Cardiomyocyte Hypertrophy

Abstract: Background-Diacylglycerol (DAG) is a lipid second messenger that transiently accumulates in cells stimulated by endothelin-1 (ET-1) and other G␣q protein-coupled receptor agonists. Diacylglycerol kinase (DGK) is thought to be an enzyme that controls the cellular levels of DAG by converting it to phosphatidic acid; however, the functional role of DGK has not been examined in cardiomyocytes. Because DGK inactivates DAG, a strong activator of protein kinase C (PKC), we hypothesized that DGK inhibited ET-1-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 50 publications
0
58
1
Order By: Relevance
“…3 In particular, numerous investigations have demonstrated the importance of the G q-mediated signaling in the development of cardiac hypertrophy and HF. 7,8,27 We previously showed that DGK inhibits GPCR agonist-induced hypertrophic signaling and resultant cardiac hypertrophy in vitro and in vivo, 16,17 and recently we also showed that DGK attenuates LV remodeling and improves survival after myocardial infarction. 28 DGK suppresses the cardiac hypertrophy and fibrosis caused by pressure overload.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…3 In particular, numerous investigations have demonstrated the importance of the G q-mediated signaling in the development of cardiac hypertrophy and HF. 7,8,27 We previously showed that DGK inhibits GPCR agonist-induced hypertrophic signaling and resultant cardiac hypertrophy in vitro and in vivo, 16,17 and recently we also showed that DGK attenuates LV remodeling and improves survival after myocardial infarction. 28 DGK suppresses the cardiac hypertrophy and fibrosis caused by pressure overload.…”
Section: Discussionmentioning
confidence: 97%
“…11 Our previous in vitro study using cultured rat neonatal cardiomyocytes has shown that DGK blocks endothelin-1-induced increases in protein synthesis concomitant with increases in cell size and reactivation of fetal genes via the inhibition of PKC . 16 In addition, DGK inhibits translocation of PKC and upregulation of ANF after GPCR agonists, such as angiotensin II and phenylephrine infusion, in mice. 17 These data are consistent with the present study's result that the inhibition of PKC by DGK might contribute to suppression of gene induction of ANF, -MHC, and BNP (Fig 5) and attenuation of increases in cross-sectional cardiomyocyte surface area (Fig 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is recent evidence that NE activates diacyglycerol kinase-leading to feedback inhibition of PKC in the caveolae/ raft fraction of rat mesenteric small arteries (48). The relevance of this finding to PKC regulation in cardiomyocytes, where a different diacyglycerol kinase isoform (namely diacyglycerol kinase-) negatively regulates hypertrophic signaling responses to G protein-coupled receptor agonists requires further study (50,51).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies of human heart failure and animal models of heart failure including genetically engineered mice have clearly shown that the activation of PKC plays a critical role under these conditions (Bowling et al 1999;Takeishi et al 1998Takeishi et al , 1999Takeishi et al , 2000, suggesting that DGK may be closely involved in the cardiac dysfunction. In this regard, DGKζ has been shown to block endothelin-1-induced activation of the PKCε -ERK-AP1 signaling pathway, atrial natriuretic factor gene induction, and resultant cardiomyocyte hypertrophy (Takahashi et al 2005). Furthermore, a recent study should be noted on the evaluation of possible roles of DGKζ in the cardiac function using an animal model of transgenic mice with cardiac-specifi c overexpression of DGKζ (DGKζ -TG) (Arimoto et al 2006).…”
Section: Animal Models and Knockout Micementioning
confidence: 99%